2017
DOI: 10.1007/s12298-017-0492-1
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of some bread wheat genotypes using molecular markers for drought tolerance

Abstract: Because of its wide geographical adaptation and importance in human nutrition, wheat is one of the most important crops in the world. However, wheat yield has reduced due to drought stress posing threat to sustainability and world food security in agricultural production. The first stage of drought tolerant variety breeding occurs on the molecular and biochemical characterization and classification of wheat genotypes. The aim of the present study is characterization of widely grown bread wheat cultivars and br… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
21
3
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 31 publications
(29 citation statements)
references
References 39 publications
4
21
3
1
Order By: Relevance
“…Previous studies show that when the PIC > 0.5, the marker has the maximum diversity, indicating high allelic diversity among germplasms. Contrarily when PIC < 0.25, the marker has minimum diversity [63,64]. Thus, these results with an average PIC value of 0.86 indicate a sufficient amount of gene variability and diversity among accessions [65].…”
Section: Discussionmentioning
confidence: 70%
“…Previous studies show that when the PIC > 0.5, the marker has the maximum diversity, indicating high allelic diversity among germplasms. Contrarily when PIC < 0.25, the marker has minimum diversity [63,64]. Thus, these results with an average PIC value of 0.86 indicate a sufficient amount of gene variability and diversity among accessions [65].…”
Section: Discussionmentioning
confidence: 70%
“…The mean number of alleles estimated in the three wheat genotypes (2.62 alleles per locus) is consistent with a study conducted by Phougat et al (2018) that found an average of 2.585 alleles per locus in 44 bread wheat genotypes using 100 SSR markers. Moreover, higher allele means numbers (5.9 and 13) were detected in 10 and 40 wheat genotypes by Ateş Sönmezoğlu and Terzi (2017) and Bousba et al…”
Section: Results and Discussion I-ssr Marker Informative And Genetic Relationshipsmentioning
confidence: 86%
“…Currently, many drought-responsive genes/proteins have been identified in different species such as wheat, maize, rice, peanut and soybean in previous studies [ 50 55 ]. These results are of great significance for exploring the molecular mechanisms and genetic improvement of wheat drought tolerance [ 56 , 57 ]. However, most of these genes/proteins have not been functionally verified, especially in hexaploid wheat.…”
Section: Discussionmentioning
confidence: 99%